Answer:
The second option, 3x^2(x+3)(4x+1)
Step-by-step explanation:
Factor out the common term, which is 3x^2
This then becomes 3x^2(4x^2+13x+3)
Factor the inside term and it becomes
(3x^2)(x+3)(4x+1)
Answer:
x = 72
Step-by-step explanation:
Make the problem simpler by eliminating the fractional coefficients:
x-9= 1/4x + (1/4x + 12) + (1/4x - 3), when multiplied by 4, becomes:
4x - 36 = x + x + 48 + x - 12
Summing up all the x terms, we get:
4x - 2x - x = 48 - 12 + 36
Then x = 72
Answer:
y=8
n=1.5
Step-by-step explanation:
Hey there,
First, find the square root of the given equation.
Keep in mind that this is solved for k = 0 and 1.
Second, simplify.
![=9\text{cos}(\frac{2\pi}{9})+i\text{sin}(\frac{2\pi}{9})~\text{or}~9\text{cos}(\frac{11\pi}{9})+i\text{sin}(\frac{11\pi}{9})](https://tex.z-dn.net/?f=%3D9%5Ctext%7Bcos%7D%28%5Cfrac%7B2%5Cpi%7D%7B9%7D%29%2Bi%5Ctext%7Bsin%7D%28%5Cfrac%7B2%5Cpi%7D%7B9%7D%29~%5Ctext%7Bor%7D~9%5Ctext%7Bcos%7D%28%5Cfrac%7B11%5Cpi%7D%7B9%7D%29%2Bi%5Ctext%7Bsin%7D%28%5Cfrac%7B11%5Cpi%7D%7B9%7D%29)
Best of Luck!